Analisa Kinerja Terminal Petikemas di Tanjung Perak Surabaya (Study Kasus: PT. Terminal Petikemas Surabaya) - Supriyono, Supriyono (Department of Civil Engineering, Diponegoro University, 2013)
Container terminal performance as a system with many variables that influence it. Results of data analysis for research activities by field survey method in 2009, were TPS performance include BOR (quay performance) 53.77% and BTP (the number of containers passing through the quay) 1.61 box/meter long pier, YOR (field performance stacking) for export 23.91% and import 55.12%. Application of model scenario analysis, the changing the length of the quay cutting the time does not operate in the dock shows the change in the performance of container terminals, among others: Scenario A, the addition of 500m quay length can reduce the density on the quay marked with: BOR 43.02% BTP 1.29 box/m, and YOR 51.96%. Scenario B, time does not operate the sip could be reduced up to 2 hours so that berth time of 20.98 hours to 18.98 hours by eliminating time off between shifts with performance:BOR 48.64%, BTP 1.45 box/m, and YOR 46.30%. Scenario C, applying the minimum service time for the entire container unloading device performance with the BOR 39.72%, BTP 1.19 box/m and YOR 18.17%.